2019
DOI: 10.1259/dmfr.20180313
|View full text |Cite
|
Sign up to set email alerts
|

Marginal bone loss and resorption of second molars related to maxillary third molars in panoramic images compared with CBCT

Abstract: Objectives: Compare findings among observers in panoramic images (PAN) and cone beam CT (CBCT); and assess findings in PAN as indicators for marginal bone loss and resorption observed in CBCT. Methods: 120 impacted maxillary third molars with PAN and CBCT were included. Four observers assessed morphological features: (1) tooth angulation; (2) number of roots; (3) bony impaction (yes/no) and pathology; (4) marginal bone level at the second molar (normal/>3 mm = bone loss); (5) resorption in the second molar (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 18 publications
4
18
1
Order By: Relevance
“…In studies using peri-apical radiographs, MxM2 was associated with ERR in 11% of the cases 26 , and in studies using panoramic imaging, this was 8% 33 and 0.3% 34 . Thus, ERR in MxM2 is clearly underdiagnosed using 2D imaging, and the superiority of CBCT scans over panoramic imaging for the diagnosis of ERR has been shown in the literature 11,14 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In studies using peri-apical radiographs, MxM2 was associated with ERR in 11% of the cases 26 , and in studies using panoramic imaging, this was 8% 33 and 0.3% 34 . Thus, ERR in MxM2 is clearly underdiagnosed using 2D imaging, and the superiority of CBCT scans over panoramic imaging for the diagnosis of ERR has been shown in the literature 11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the examination and clinical experience, the clinician will decide whether adjunctive CBCT imaging may provide further important information. Information about the localization and severity of ERR based on CBCT scans should facilitate the decision-making process, with options being conservative treatment of MxM2, prophylactic removal of MxM3, or removal of MxM2 instead of MxM3 11,14 . An irreversible pathology, such as severe ERR on MxM2 related to MxM3, is an indication for removal of MxM3 and sometimes MxM2 as well 6 or instead 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study has shown that panoramic imaging was not able to predict ERR when compared to a three-dimensional radiographic method, cone beam CT (CBCT), while panoramic imaging was to some extent able to predict marginal bone loss. 2 Nonetheless, CBCT exposes the patient to a higher radiation dose and involves higher costs for the patient and society than panoramic imaging, 3,4 and for that reason it is important only to perform a CBCT examination on evidence-based indications. While many studies are available on the impact of CBCT in assessing mandibular third molars prior to removal, [5][6][7][8] very few studies exist in the literature on maxillary third molars.…”
Section: Introductionmentioning
confidence: 99%